Induction motor rotor bars type effects towards energy efficiency, economic and environment - Yanawati Yahya; Mohd Khairil Rahmat (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Nowadays, the rotating motor is the most demoralized machine for the global Motor industry. Comfort of practice, start-up, small, weightiness, Increased efficiency, low maintenance and inexpensive for each power rating that generally meets the necessary features for industries. Efficient improvements are inspected with copper for the rotor bars slot. Usually, the copper loss in the induction motor Rotor division contributes to the loss of energy. The research work was planned a new rotor design, by improved rotor bars type slot, size and design. These tasks were inspected using two approaches, in particular, MotorSolve (IM) and calculations in theory. One set of simulation has shown a significant increase in energy efficiency for a new rotor frame design. Calculations in theory are used MATLAB. As a result, these new designs have improved energy efficiency by 77% as compared to its 74% existing design. The results proved to be using MATLAB. For energy, cost savings and emission reduction (ER), new design rotor frame has been saved 154KWH/year, utility bill RM 60.20/Year and 0.113 CO2 tons/years intended for individually motor. Finally, the estimated cost aimed at 100,000 pieces of new rotor bars pattern induction motor and indicates this price was kept almost RM6 million.